Assessment of post-operative pain, swelling and trismus following mandibular third molar extraction after local administration of dexamethasone - a retrospective study - DEVI G, KARTHIGA; PRADEEP D (The journal of contemporary issues in business and government, 2020)
The aim of this study was to assess the post operative pain, swelling and trismus following mandibular third molar extraction after local administration of dexamethasone. This study was conducted among 142 patients who had undergone surgical removal of mandibular third molar reported to a private dental hospital from June 2019 to March 2020 . Data was collected and tabulated in excel. Data was analysed using SPSS version 20 . Results of this study showed that among 142 patients, consisting of 63 females (44.37%) and 79 males (55.63%). There was no statistically significant association between age, gender, tooth number and dexamethasone. Patients experienced less postoperative pain, swelling and trismus after local administration of dexamethasone. We conclude from the present study that the dexamethasone decreases the pain, swelling and trismus following mandibular third molar extraction.